2014
DOI: 10.1111/tri.12466
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between virus-related factors and post-transplant ascites in patients with hepatitis C and no cirrhosis: role of cryoglobulinemia

Abstract: SummaryRefractory ascites may appear in liver transplant recipients with recurrence of hepatitis C virus infection, even in the absence of advanced fibrosis. The mechanisms are unclear. The aim was to determine whether post-transplant cryoglobulinemia could be a predisposing factor for ascites in this population. Retrospective data of 82 liver transplant recipients with HCV recurrence surviving more than 1 year were collected. Cryoglobulinemia was systematically tested after transplantation. All patients had 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Then, nonsignificant predictor variables were sequentially eliminated and models re‐estimated until all variables remaining in the model show significant association with the outcome. The technique of backward selection is sometimes also applied directly to a set of predictor variables , or the process of variable selection is reversed by “forward selection” , meaning that candidate predictors are sequentially included in a model if their association with the outcome variable, on top of the set of variables already in the model, is significant. Box provides an overview of the most common approaches of variable selection and explains some statistical notions commonly used in this context.…”
mentioning
confidence: 99%
“…Then, nonsignificant predictor variables were sequentially eliminated and models re‐estimated until all variables remaining in the model show significant association with the outcome. The technique of backward selection is sometimes also applied directly to a set of predictor variables , or the process of variable selection is reversed by “forward selection” , meaning that candidate predictors are sequentially included in a model if their association with the outcome variable, on top of the set of variables already in the model, is significant. Box provides an overview of the most common approaches of variable selection and explains some statistical notions commonly used in this context.…”
mentioning
confidence: 99%
“…5,9 Positive cryoglobulinemia in HCV-positive patients was also found to be predictive of ascites development. 9 There are limited data on ascites resolution after HCV treatment, particularly with use of DAAs. However, in our experience, ascites generally resolves after HCV treatment if advanced fibrosis is not present.…”
Section: An Official Learning Resource Of Aasldmentioning
confidence: 97%
“…HCV recurrence after liver transplantation can result in ascites even in the absence of significant fibrosis. According to two retrospective studies, ascites was found in patients with stage 0, 1, or 2 fibrosis on allograft biopsy 5,9 . Positive cryoglobulinemia in HCV‐positive patients was also found to be predictive of ascites development 9 .…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Lan et al [ 18 ] among 173 hepatitis C virus (HCV) transplants, 18 patients (10%) developed posttransplant ascites, with two-thirds of ascites episodes occurring without significant fibrosis. In the retrospective study of 82 liver transplant recipients with HCV recurrence, 17% of patients developed refractory ascites, and in some patients, refractory ascites occurred in the absence of advanced fibrosis[ 19 ]. In the same study, positive cryoglobulinemia that was systematically tested (P = 0.02) and perisinusoidal fibrosis at 1 year ( P = 0.02) were independently associated with posttransplant ascites[ 19 ].…”
Section: Etiologymentioning
confidence: 99%